UROLOGICAL PROBLEM AFTER GYNECOLOGICAL SURGERY - Muhammad Khalid; Imran Karim Jaskani (Journal of University Medical & Dental College, 1970)
ABSTRACT We report an unusual case of hanging bladder stone which formed on a non absorbable suture in a woman with previous abdominal hysterectomy. She was investigated thoroughly for recurrent UTI and found to have urinary bladder stone. After endoscopic unsuccessful attempt for stone crushing vesicolithotomy was done and a stone was recovered with a piece of suture. Based on literature most of foreign bodies in the bladder are subject to stone formation on the bladder wall, but in this case stone was hanging with the dome of bladder while rest of bladder wall was healthy. We suggest that bladder stone should be excluded in the woman with recurrent lower urinary tract infection. Therefore thorough history and complete investigations in addition to urine analysis, X-RAY and USG must be done in every case.